Augmented reality for story-related activities in primary and secondary education: a systematic review - Christou, Eirini; Parmaxi, Antigoni; Farrugia Caruana, Lawrence; Busuttil, Leonard; Żammit, Jacqueline; Rodríguez-Cano, Sonia; Delgado-Benito, Vanesa; Alonso-Martínez, Laura; Ioannou, Andri (My University, 2026)
Story-related activities such as storytelling, story creation and narrative-based learning have become a popular pedagogical approach used in education. Additionally, Augmented Reality (AR) is a tool that receives significant attention globally. Recognizing this trend, researchers have been seeking ways to integrate story-related activities with AR in educational contexts. This paper presents a systematic literature review focusing on the use of AR in story-related activities within primary and secondary education. By conducting a systematic search of studies published in the past 5 years between 2019 and 2024, 264 relevant papers were initially identified. After applying inclusion, exclusion and quality criteria, 39 studies were selected for in-depth analysis. Framed by the principles of learning experience design, this review explores how AR is integrated into story-based educational practices, highlighting its current applications, benefits, and barriers. Additionally, the review critically reflects on the need to prioritise pedagogy over technological features when designing AR-enhanced learning experiences. The study concludes with recommendations for future research and practical insights for educators aiming to incorporate AR into story-related educational activities.